2016
DOI: 10.1371/journal.pone.0165360
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Acute Hepatocellular Injury Afforded by Liver Fibrosis Is Independent of T Lymphocytes

Abstract: Collagen produced during the process of liver fibrosis can induce a hepatocellular protective response through ERK1 signalling. However, the influence of T cells and associated cytokine production on this protection is unknown. In addition, athymic mice are frequently used in hepatocellular carcinoma xenograft experiments but current methods limit our ability to study the impact of liver fibrosis in this setting due to high mortality. Therefore, a mouse model of liver fibrosis lacking T cells was developed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, the SERS band of amide III at 1261 cm −1 in serum protein of HBV patients groups shows higher signal intensity than in normal samples, because the amide III band has been shown to be sensitive to protein secondary structure [21]. The prominent SERS peak located at around 1207 cm −1 is ascribed to the appearance of hydroxyproline, as an important product of collagen metabolism, whose content is associated with the development of liver fibrosis (as a complication of HBV infection) [22, 23]. The SERS peak of phenylalanine at 1007 cm −1 and the ring breathing of tyrosine at 1160 and 1178 cm −1 showed higher normalised intensity in the HBV patients groups.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the SERS band of amide III at 1261 cm −1 in serum protein of HBV patients groups shows higher signal intensity than in normal samples, because the amide III band has been shown to be sensitive to protein secondary structure [21]. The prominent SERS peak located at around 1207 cm −1 is ascribed to the appearance of hydroxyproline, as an important product of collagen metabolism, whose content is associated with the development of liver fibrosis (as a complication of HBV infection) [22, 23]. The SERS peak of phenylalanine at 1007 cm −1 and the ring breathing of tyrosine at 1160 and 1178 cm −1 showed higher normalised intensity in the HBV patients groups.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of T cells, different T-cell subpopulations play different roles in the process of liver fibrosis. Previous studies have reported that T-cell impairment generally does not alter fibrogenesis, while Th2 and Th17 CD4 + T cells are involved in the inflammatory process, promoting cytokine production and HSC activation[ 36 ]. Here, the ratio of CD4 + T cells and CD8 + T cells was upregulated in the liver and spleen (data not shown), but the activation of these T cells was not significantly affected by Fasudil treatment (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%